Jens Lei Wendel Hansen, Grönlands Amt (Aarhus: Aarhus University Press, 2019) - Guðmundur Alfredsson (Nordicum-Mediterraneum, 2020)
A review of the book: Jens Lei Wendel Hansen, Grönlands Amt (Aarhus: Aarhus University Press, 2019)